Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Purpose ORCHARD (NCT03944772) was a phase II, open-label study evaluating resistance mechanisms and post-progression therapies in patients with epidermal growth factor receptor (EGFR)-mutated advanced non-small cell lung cancer (NSCLC) with progressive disease (PD) on first-line osimertinib. We report final data from the osimertinib plus gefitinib module in patients with EGFR C797X, a known resistance mechanism to osimertinib. Methods Patients received once daily osimertinib 80 mg plus gefitinib 250 mg until PD, unacceptable toxicity, or another discontinuation criterion. Primary end point was objective response rate (ORR) by investigator per RECIST 1.1. Results Thirty-one patients were treated and evaluable for response/safety (data cutoff: May 10, 2024). Eight patients had a partial response, for a confirmed ORR of 26% (80% confidence interval [CI]: 16-39); median duration of response was 4.2 months (95% CI: 2.8-5.5). Thirty patients (97%) experienced a progression-free survival (PFS) event and 19 patients (61%) died. Median PFS was 5.1 months (95% CI: 3.9-6.8) and median overall survival was 19.0 months (95% CI: 14.6-25.0). Eleven patients (35%) had grade ≥3 adverse events. Safety was consistent with the known adverse-event profiles of the individual drugs, with no new safety signals. Several resistance mechanisms (EGFR T790M, BRAF, and PIK3CA mutations) were identified following PD on osimertinib-gefitinib. Conclusions Osimertinib-gefitinib demonstrated modest clinical benefit in patients with EGFR-mutated advanced NSCLC harboring an EGFR C797X mutation identified following PD on first-line osimertinib. The risk-benefit profile indicates that further evaluation of this regimen is not warranted in this population.